2014
DOI: 10.11646/zootaxa.3872.5.5
|View full text |Cite
|
Sign up to set email alerts
|

One new species of Micronephthys Friedrich, 1939 and one new species of <br />Nephtys Cuvier, 1817 (Polychaeta: Phyllodocida: Nephtyidae) <br />from eastern Australia with notes on Aglaophamus australiensis (Fauchald, 1965) and a key to all Australian species

Abstract: There are currently over 130 described species of Nephtyidae worldwide, with 18 species known from Australian waters belonging to four genera. Two new species are described, Micronephthys derupeli n. sp., and Nephtys triangula n. sp., from Eastern Australia. Descriptions are provided for all species examined. Comments are given about the recent transfer of Nephtys australiensis to Aglaophamus. A key to all Australian species of nephtyids is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…Remarks. As remarked by Dixon-Bridges et al (2014), following the modified generic diagnosis of Ravara et al (2010b), some branchiate Micronephthys species that lack lyrate chaetae may be mistaken for small or juvenile Nephtys specimens. However, reduced or rudimentary parapodial lobes and few pairs of branchiae are features of such Micronephthys species, and as such should distinguish them from Nephtys specimens, in which well developed parapodial lobes and numerous branchiae exist even in small specimens.…”
Section: Genus Micronephthys Friedrich 1939mentioning
confidence: 99%
See 4 more Smart Citations
“…Remarks. As remarked by Dixon-Bridges et al (2014), following the modified generic diagnosis of Ravara et al (2010b), some branchiate Micronephthys species that lack lyrate chaetae may be mistaken for small or juvenile Nephtys specimens. However, reduced or rudimentary parapodial lobes and few pairs of branchiae are features of such Micronephthys species, and as such should distinguish them from Nephtys specimens, in which well developed parapodial lobes and numerous branchiae exist even in small specimens.…”
Section: Genus Micronephthys Friedrich 1939mentioning
confidence: 99%
“…The most diverse genera both worldwide and in Australia are Aglaophamus and Nephtys, with eight and seven species now known in Australia respectively. Micronephthys is represented in Australia by three species and Inermonephtys by two species (Dixon-Bridges et al 2014) whereas Bipalponephtys has not yet been reported from Australia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations